The workshops and festival of Brazilian culture and music of the University of Glasgow as an initiative for cultural promotion and integration - Ribeiro, Gabriela Castelo Branco; de Souza, José Peixoto Coelho (BELT - Brazilian English Language Teaching Journal, 2019)
The aim of this paper is to present and reflect on the project “Workshops of Brazilian Culture and Music”, done in 2015 and 2016 by the Portuguese Programme of the University of Glasgow. Motivated by the interest of students of Portuguese in Brazilian music and by the recognition of its cultural richness and pedagogical potential (Barbosa (2001), Hermeto (2012), Coelho de Souza (2014)), the project focused on musical, cultural, historical, artistic and intercultural elements of Brazilian popular music in seven sessions and a festival. The workshops and festival attracted a varied audience, receiving very positive feedback from participants, with a potential to have a positive impact for the University, the School of Modern Languages and Cultures and the Portuguese Programme. With this paper, we expect to contribute to the discussion and effective implementation of initiatives which foster the promotion of the Portuguese language and Lusophone cultures and create interest in the study of the language.